Abnormal Proventriculus in Bumble Bee Males - Mario X. Ruiz-González (Diversity, 2022)
Females social insects are widely investigated, while males are often neglected. Previous work on the morphology of the bumble bee male alimentary tract has described the presence of swollen proventriculi as a character with taxonomic value. New observations suggest that the abnormal proventriculus might be an abnormal condition. Here, I identify a potential health issue in bumble bee (Hymenoptera: Apidae: Bombus) male alimentary tracts that consists of a swollen and strongly melanized proventriculus, thereby preventing the normal passage of food through the esophageal valve. Males from three bumble bee species exhibited the abnormal proventriculus with an overall prevalence of 31.1% across two years. This finding challenges previous research that suggested the swollen and melanized proventriculus of Bombus males as a taxonomic character.